Potential Pathway for Reliable Long-Term CO2 Storage as Clathrate Hydrates in Marine Environments - Beatrice Castellani (Energies, 2023)
A countermeasure to global warming is removing high CO2 amounts from the atmosphere and locating the emitted CO2 into long-term stable carbon storage sites. The sequestration technologies must be reliable, long-lasting, and environmentally friendly. An alternative and innovative approach that may meet the sequestration requirements is CO2 storage as clathrate hydrates in marine environments. Extensive research has been devoted to CO2-CH4 replacement in natural gas hydrates. Another option is the direct formation of CO2 hydrates into deep ocean water or into marine underfloor sediments. This article deals with the positioning of direct hydrate-based CO2 storage among the other traditional geological options and the discussion of new, by-far, state-of-the-art knowledge required for the development of a hydrate-based CO2 storage pathway that is reliable, stable, durable, efficient, and environmentally benign.